Toribio de Astorga, "Epistula ad Idatium et Ceponium" (CPL 564): edición crítica - Martín-Iglesias, José Carlos 1968-; Iranzo Abellán, Salvador (2015)
The Epistula ad Idatium et Ceponium (CPL 564) of Turibius of Astorga (5th century), about heresies and apocryphal books circulating in fifth-century Spain, has been transmitted in a single manuscript, the current Toledo, BC, 27-24 (T), from the sixteenth century. The editio princeps of A. Morales is based on a codex of San Lorenzo de El Escorial from San Millan dating back to the eleventh century, which has disappeared. This lost manuscript is the model from which the current Toledo manuscript was copied. This article offers the first critical edition of the letter of Turibius, based on the testimony of T and Morales’ edition. An exhaustive description of the contents of T and a linguistic study of the text precede the edition, and a translation is added.
Keywords: Toribio de Astorga, -- Santo, -- Obispo de Astorga; Crítica textual